DAMPAK SISTEM KEUANGAN SYARIAH TERHADAP PEMBANGUNAN EKONOMI DI NEGARA BERKEMBANG - Siti Nurhalizzah; Lucy Mareta; Nur Musyarofah; M. Masrukhan (Cahaya Ilmu Bangsa, 2024)
This article analyzes the impact of the Islamic financial system on economic development, particularly in developing countries. Through qualitative and quantitative approaches, this study explores the core principles of Islamic finance, its products and services, and comparisons with conventional financial systems. The findings reveal that Islamic finance significantly contributes to financial inclusion, poverty alleviation, and economic growth. It also enhances economic stability by minimizing speculative activities and encouraging productive investments. Notably, this research highlights the system’s unique ability to leverage the economic potential of Muslim communities while attracting ethically and morally driven investors. The results underscore Islamic finance as a pivotal catalyst for sustainable development in developing countries.